Corporatization and Mission in Higher Education - Hansen, Morten (International Higher Education, 2025)
Corporatization in higher education is often equated with institutional mission drift. To complicate this perspective, this paper claims that importing private-sector practices can bolster institutional mission rather than only undermine it. Drawing on recent research on international foundation programs, this claim is tested through three scenarios.